HUBUNGAN ANTARA EDUKASI HADIS QUDSI DENGAN KARAKTER RELIGIUS PADA KOMUNITAS KAJIAN KEISLAMAN PROBOLINGGO - Irfan Yuhadi; Nurul Budi Murtini; Muhammad Yassir (Al-Majaalis : Jurnal Dirasat Islamiyah, 2022)
Education is a virtue that makes scientific regeneration work. Through education the quality of understanding can be improved. So that slowly the ignorance that exists in a community can be eliminated. Social change can be realized through continuous education. Especially if the education given to the community is qudsi hadith that are sourced from the holy word of Allah. Hadith qudsi education is teaching and educating others about the hadith qudsi narrated by the Prophet – may Allah’s peace and blessings be upon him – from Allah the Exalted and Glorious, while religious character is a religious trait that is inherent and manifests in behavior and actions. The approach used in this study is a quantitative approach with the type of correlational research to determine the correlation between hadith qudsi education and religious character. The population of this research is the Islamic Lectures community in Probolinggo. The number of samples in this study were 30 people taken by simple random sampling technique. The results showed that there was a significant positive correlation between hadith qudsi education and religious character in the Probolinggo Lecture community, so that the higher the education of hadith qudsi, the higher the religious character. The level of correlation between hadith qudsi education and religious character is a strong correlation.